ANALISIS CORPORATE SOCIAL RESPONSIBILITY DIPENGARUHI UKURAN PERUSAHAAN, UMUR PERUSAHAAN DAN PROFITABILITAS - Medy Desma Fatwara; Ahmad Nurdin Hasibuan; LM Nursalam; Zara Tania Rahmadi (Universitas Prof. Dr. Moestopo (Beragama), 2022)
This study aims to determine CSR which is influenced by Size, Company Age, and Profitability. The data used in the study is secondary data using the purposive sampling method or deliberately obtained a sample of 8 companies listed on the LQ 45 Index on the IDX in 2016-2019. The analysis technique used in this research is multiple linear regression. The results show that company age has a significant positive effect on CSR, while company size and profitability have no effect. Meanwhile, simultaneously there is a significant influence on CSR..